Paraplegia and acute aortic dissection: a diagnostic challenge for physicians in the emergency situation. Issue 7 (8th July 2019) - Memon, Waqas; Aijaz, Zobia; Memon, Rmaah
Abstract : Acute aortic dissection presenting neurological symptoms is rare and entails significant diagnostic challenges. We present a case of 45-year-old woman with a medical history of essential hypertension and smoking, admitted with lobar pneumonia. During her inpatient treatment, she developed severe back pain and numbness below the level of the umbilicus. Due to her presenting symptoms considered differential diagnoses were paravertebral abscess and acute stroke. CT scan of the head did not reveal any ischaemic changes. Further investigation with MRI (with and without contrast) raised concerns for possible aortic dissection. CT angiography of thorax, abdomen and pelvis displayed extensive aortic dissection extending from aortic root to left iliac artery limiting flow to right carotid artery causing stenosis. The patient was diagnosed with Stanford type A aortic dissection. The patient was referred to the cardiothoracic surgery team for surgical repair. The patient made a good recovery after a prolonged course of hospitalisation, followed by cardiac rehabilitation and physical therapy.